High-energy-impact-resistant heating substrate for thermal printing head and manufacturing method thereof

A multilayer thermal printing head substrate with HfRe/HfIr electrodes and HfO2/SiN/SiON protection layers addresses the thermal and mechanical challenges of thermal printing heads, ensuring high thermal resistance and electrical conductivity.

CN119872085AActive Publication Date: 2025-04-25SHANDONG HUALING ELECTRONICS

Patent Information

Application Number
CN202411684017.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Existing thermal printing heads face challenges in achieving high thermal resistance and electrical conductivity while withstanding high energy impacts, as existing materials like HfCxNy and Ta-based coatings are inadequate for the extreme temperatures and mechanical stress encountered in thermal printing.

Method used

A thermal printing head substrate with a multilayer structure comprising a ceramic-based insulation layer, a dual-layered electrode structure using HfRe and HfIr alloys, and a protective layer made of HfO2 and SiN/SiON/SIALON materials, ensuring thermal compatibility and mechanical resilience.

Benefits of technology

The substrate significantly enhances thermal resistance and mechanical durability, preventing layer delamination due to thermal expansion mismatch, while maintaining electrical conductivity and high-temperature stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872085A_ABST
    Figure CN119872085A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal printing head manufacturing, in particular to a high-energy-impact-resistant heating substrate for a thermal printing head and a manufacturing method of the high-energy-impact-resistant heating substrate, and the high-energy-impact-resistant heating substrate can improve the energy impact resistance of a product. A lower-layer electrode wire and an upper-layer electrode wire are arranged in the high-energy-impact-resistant electrode wire section, the lower-layer electrode wire is made of hafnium-rhenium HfRe alloy, the thickness range of the lower-layer electrode wire is 0.1-2.0 microns, the content of hafnium Hf in the lower-layer electrode wire accounts for 10% or below of the total mass percentage, the upper-layer electrode wire is made of hafnium-iridium alloy, and the thickness range of the upper-layer electrode wire is 0.1-2.0 microns. The upper-layer electrode wire is located on the surface of the lower-layer electrode wire, the thickness range of the upper-layer electrode wire is 0.05-0.2 mu m, and the content of hafnium Hf in the lower-layer electrode wire accounts for 10% or below of the total mass percentage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the technical field of thermal print head manufacturing, in particular to a heating substrate for a thermal print head capable of improving the energy impact resistance of the product and a manufacturing method thereof. Background technology:

[0002] The thermal print head is a component that prints using Joule heat. During printing, the temperature of the printing area is very high, and in special circumstances it can reach over 1000°C. The existing thermal print heads are difficult to meet this requirement due to their high temperature resistance.

[0003] The invention of patent document CN102815971 discloses a Hf(Ta)C ultra-high temperature multiphase coating, which is composed of HfC and HfTaC2, wherein the mole fraction of HfTaC2 is 6-50%, and is evenly or gradiently distributed in the coating. The preparation method is to place the surface-treated substrate in a low-pressure chemical vapor deposition furnace, use a mixed powder of hafnium tetrachloride and tantalum pentachloride as the hafnium source and tantalum source; methane as the carbon source; argon as the diluent gas; hydrogen as the reducing gas, transport the mixed powder to the inside of the deposition furnace reactor, and deposit the Hf(Ta)C ultra-high temperature multiphase coating on the surface of the substrate.

[0004] Patent document CN109320303 provides an ultra-high temperature oxidation-resistant and ablation-resistant coating and a preparation method thereof, and relates to the field of chemical vapor deposition technology. The present invention provides an ultra-high temperature oxidation-resistant and ablation-resistant coating, including a Ta / (Ta, Hf)C multi-layer multiphase composite coating formed by alternating superposition of a metal Ta coating and a (Ta, Hf)C multiphase coating. A method for preparing an ultra-high temperature oxidation-resistant and ablation-resistant coating is also provided, and the steps are as follows: S01, providing a pretreated substrate material; S02, preparing a (Ta, Hf)C multiphase coating on the surface of the substrate material, preparing a metal Ta transition coating on the surface of the (Ta, Hf)C multiphase coating, alternating deposition for multiple times, and finally ending the deposition with a (Ta, Hf)C multiphase coating to prepare a Ta / (Ta, Hf)C multi-layer multiphase composite coating. It is suitable for preparing ultra-high temperature protective coatings on the inner pore surfaces of substrates such as graphite and C / C composite materials, and improving the oxidation resistance, ablation resistance, and thermal shock resistance of the inner pore working surface of the substrate material.

[0005] Patent document CN109972120 relates to a method for preparing a multi-component composite carbide coating. It includes the following steps: (1) placing a mixed powder of TaCl5, HfCl4 and ZrCl4 in a crucible under an inert atmosphere; (2) placing a substrate sample on a support of a deposition furnace, introducing argon gas, and heating to a deposition temperature; (3) placing the crucible containing the mixed powder on a lifting support of a low temperature zone in a dual-temperature zone gasification furnace, connecting the crucible mouth with the high temperature zone, setting the heating temperatures of the low and high temperature zones, and heating to completely vaporize the mixed powder; (4) introducing H2 and CH4 into the deposition furnace, and introducing the completely vaporized mixed gas into the deposition furnace with a carrier gas, and depositing under normal pressure. This preparation method can obtain a multi-component composite coating with an accurate stoichiometric ratio of each component, and can ensure that the coating is tightly and firmly bonded to the substrate material and has excellent stability.

[0006] Patent document CN111072388B, relates to a long-term ablation-resistant ultra-high melting point nitrogen-containing carbide ultra-high temperature ceramic and its application, and provides a method of using ball milling + spark plasma sintering to prepare HfCx Ny ceramics with a density greater than or equal to 98% and a uniform C / N content distribution. The designed and prepared new ultra-high melting point ceramic overcomes the defects of existing ultra-high temperature ablation-resistant ceramics, such as too low ablation resistance temperature or too fast high temperature ablation loss; making it suitable for ultra-high temperature ablation protection of 3000℃ and above.

[0007] The above documents all involve the research of Hf(Ta)C or HfCxNy high temperature resistant coatings. However, the electrode wire components and heating resistor components of the thermal print head must meet the requirements of heat resistance and conductivity at the same time. The existing hafnium carbon nitride compounds and related materials cannot be directly used in the manufacture of thermal print heads. Summary of the invention:

[0008] In view of the shortcomings and deficiencies in the prior art, the present invention proposes a heating substrate for a thermal print head that is resistant to high energy impact and can improve the energy impact resistance of the product, and a manufacturing method thereof.

[0009] The present invention is achieved by the following measures:

[0010] A heating substrate for a thermal print head resistant to high energy impact is provided, comprising an insulating substrate, an underglaze layer on the insulating substrate, a heating resistor and an electrode wire arranged on the underglaze layer, and a protective layer covering the heating resistor and part of the electrode wire, characterized in that the electrode wire comprises an electrode wire segment resistant to high energy impact, the electrode wire segment resistant to high energy impact is provided with a lower electrode wire and an upper electrode wire, the lower electrode wire is made of a hafnium-rhenium HfRe alloy, the thickness of the lower electrode wire is in the range of 0.1-2.0 μm, and the content of hafnium Hf in the lower electrode wire is less than 10% of the total mass percentage, and the upper electrode wire is made of a hafnium-iridium alloy, the upper electrode wire is located on the surface of the lower electrode wire, and the thickness is in the range of 0.05-0.2 μm, and the content of hafnium Hf in the lower electrode wire is less than 10% of the total mass percentage.

[0011] The electrode wire of the present invention also includes a common wire segment connected to the electrode wire segment resistant to high energy impact, the common wire segment is made of aluminum wire, and the electrode wire segment resistant to high energy impact is only distributed in the area 0.3 mm away from the heating resistor.

[0012] The heating resistor of the present invention is made of a mixture of HfCxNy and SiC, wherein the proportion of HfCxNy is between 30% and 70%, the thickness of the heating resistor is 10 to 500 nm, and the resistivity of the heating resistor is 500 to 4000E-8Ω.m.

[0013] The base glaze layer of the present invention comprises a base glaze heat storage layer using SiO2 as the main material and a HfO2 layer located on the upper surface of the base glaze heat storage layer, the thickness of the base glaze heat storage layer is between several um and several hundred um; the thermal conductivity of the base glaze heat storage layer is 1±0.5W / mK, and the thermal expansion coefficient is 6.5±1e-6 / ℃; a HfO2 layer with a thickness of 0.1~10um is provided on the surface of the base glaze heat storage layer, and the melting point of HfO2 is 2758℃, which can improve the power resistance and temperature resistance of the print head; the thermal conductivity of the HfO2 layer is 1.6~2W / mK, and the thermal conductivity similar to that of the base glaze heat storage layer can maintain similar thermal response characteristics, and the thermal expansion coefficient of HfO2 is 6±1e-6 / ℃, and the similar thermal expansion coefficient can avoid interlayer peeling due to thermal expansion and contraction.

[0014] The insulating protective film in the protective layer of the present invention is composed of at least one of a HfO2&SiN mixture, a HfO2&SiON mixture, or a HfO2&SIALON mixture, the proportion of HfO2 is less than 20%, the total thickness is between 1 and 20 um, SiN is an electrical insulating material, the temperature resistance is about 1900°C, and the thermal expansion coefficient is 2.35±0.5e-6 / °C; SIALON is an electrical insulation material, the melting point is greater than 1500°C, the heat shock resistance is greater than 900°C, and the thermal expansion coefficient is 2.6±0.5e-6 / °C. Both are excellent temperature-resistant materials, and the expansion coefficient is close to that of the HfO2 layer in the bottom glaze layer and the HfCxNy material in the heating resistor. The similar thermal expansion coefficients can avoid interlayer peeling due to thermal expansion and contraction.

[0015] The present invention also proposes a method for manufacturing a heating substrate for a thermal print head as described above, characterized in that the heating element layer resistant to high-energy impact is made by a PVD or CVD process, the heating resistor layer is made of a mixture of HfCxNy and SiC, and then a photolithography process is adopted, photoresist is used as a protective layer, and dry etching is performed to form a resistor layer pattern, and the etching gas is selected from Ar, CF4, CHF3, O2, etc.; the electrode wire segment resistant to high-energy impact can be made by two methods. The first method is to first make an electrode wire layer by a PVD or CVD process, and then a photolithography process is adopted to cover the unnecessary pattern with photoresist and wet etching is performed to form a wire pattern; the second method is to first cover the surface of the resistor pattern with photoresist, and then perform photolithography and development, and then make an electrode wire layer by a PVD or CVD process, and finally remove the photoresist and the electrode wire layer above to form an electrode wire pattern. Here, since the resistor layer is generally very thin, it is not easy to be placed on top of the electrode to avoid wire breakage due to the step difference.

[0016] In the method for manufacturing a heating substrate for a thermal print head of the present invention, the heating resistor is manufactured by the following method:

[0017] Step 1: Prepare HfC powder, HfN powder and SIC powder according to the mass ratio of HfC:HfN:SIC=(1-3):(1-3):(1-2), and the specific ratio is adjusted according to the resistance value of the print head to be made. The purity of HfC, HfN and SIC is greater than or equal to 99.9%. The prepared HfC powder, HfN powder and SIC powder are refined by ball milling and mixed evenly. The mixed powder is filtered to obtain a powder with a particle size of less than 5um;

[0018] Step 2: Plasma sintering of the obtained mixed powder, the conditions of plasma sintering are: the temperature in the sintering furnace is 2100-2500° C., the temperature is kept for 15-20 minutes, the pressure is 35-50 MPa, and the vacuum degree is less than 2 Pa;

[0019] Step 3: The sintered material is cut into required sizes and welded to the target base to make a PVD target;

[0020] Step 4: Use PVD magnetron sputtering technology to prepare the heating resistor layer by direct current DC or radio frequency RF, put the substrate with base glaze into the cavity, set the vacuum degree in the cavity to below 1×10-4Pa, heat the cavity temperature to 150~300℃, and introduce argon gas with a pressure of 0.1~5Pa.

[0021] In step 4 of the present invention, since the material is conductive, direct current (DC) is preferred, and the sputtering efficiency is higher. The film layer is prepared using magnetron sputtering technology. In order to improve the density and adhesion of the material, a direct current pulse method can be further adopted on the basis of the DC mode. The conditions are a frequency of 50-150k, a pulse power density of 4-7w / cm2, a duty cycle of 20-45%, and an air pressure of 0.2-0.8Pa; or high-power pulsed magnetron sputtering (HIPIMS) technology is adopted, with a pulse power density of 400-1000w / cm2, a frequency of 0.1-5kHz, a duty cycle of 5-20%, and an air pressure of 0.2-1Pa.

[0022] The base glaze layer and the electrode layer of the present invention can be prepared by directly sputtering the corresponding target materials; the electrode is a conductive material and can be prepared by DC or RF magnetron sputtering process; the base glaze heat storage layer is a non-conductive material and is prepared by RF magnetron sputtering process; the preparation method of the protective layer can be obtained by single-target sputtering, and the single target is prepared by mixed plasma sintering method, or two independent double targets are used. When sputtering two independent target materials, the method of sputtering in the same cavity can be adopted according to different proportions. Because the target material is non-conductive, the protective layer is prepared by RF magnetron sputtering process.

[0023] Compared with the prior art, the present invention significantly improves the heat resistance of the product by providing an electrode wire segment resistant to high-energy impact, and further correspondingly provides a heating resistor, a base glaze layer and a protective layer resistant to high-energy impact, and can meet the conductivity requirements of the corresponding devices. From the heat storage layer to the heating element, to the electrode, and then to the protective layer, the Hf element runs through the entire process, which can maintain the fusion between the layers, and the thermal expansion coefficients between related components are similar, thereby effectively overcoming the problem of interlayer peeling caused by thermal expansion and contraction. Description of the drawings:

[0024] Attached Figure 1 It is a cross-sectional view of a heating substrate for a thermal print head in the present invention.

[0025] Attached Figure 2 It is a schematic diagram of the local structure of the electrode wire in the present invention.

[0026] Attached Figure 3It is a partial cross-sectional view of the heating resistor region of the heating substrate for the thermal print head of the present invention.

[0027] Figure numerals: insulating substrate 1, base glaze layer 2, base glaze heat storage layer 2-1, HfO2 layer 2-2, heating resistor 3, electrode layer 4, lower electrode line 4-1, upper electrode line 4-2, common electrode 4a, individual electrode 4b, protective layer 5. Specific implementation method:

[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0029] Example:

[0030] This example provides a heating substrate for a high energy-resistant thermal print head, comprising an insulating substrate 1, a base glaze layer 2, a heating resistor 3, individual electrodes 4b, a common electrode 4a, and a protective layer 5, wherein the protective layer 5 is provided with an insulating protective layer, and a wear-resistant protective layer can be added on the insulating protective layer as needed;

[0031] In this example, the base glaze layer 2 adopts a composite structure of a base glaze heat storage layer 2-1 with SiO2 as the main material and a HfO2 layer 2-2; the heating resistor 3 is composed of a mixture of HfCxNy and SIC, and the components include at least two kinds of conductive materials and insulating materials, so that the resistivity of the heating resistor can be adjusted by proportion; some electrode wires (electrode wire segments resistant to high-energy impacts) adopt a double-layer structure, the lower electrode wire is composed of Hf+Re alloy, and the upper electrode wire is composed of Hf+Ir alloy; the insulating protective layer in the protective layer is composed of at least one of a HfO2&SiN mixture, a HfO2&SiON mixture, or a HfO2&SIALON mixture.

[0032] In this example, the base glaze heat storage layer 2-1 is made of a mixture of compounds composed of common base glaze materials such as Si, O, B, Zr, Ca, Al and other elements, and is prepared by printing and sintering thick film technology, with a thickness of several um to several hundred um; the thermal conductivity of the base glaze heat storage layer is about 1W / mK, and the thermal expansion coefficient is 6.5±1e-6 / ℃; the HfO2 layer 2-2 is made on the surface of the base glaze heat storage layer by PVD, CVD and other processes, with a thickness of 0.1~10um, and the melting point of HfO2 is 2758℃, which can improve the power resistance and temperature resistance of the print head; the thermal conductivity of the HfO2 layer 2-2 is 1.6~2W / mK, and the thermal conductivity similar to that of the lower layer can maintain similar thermal response characteristics, and the thermal expansion coefficient of HfO2 is 6±1e-6 / ℃. The similar thermal expansion coefficients can avoid interlayer peeling due to thermal expansion and contraction.

[0033] The heating resistor 3 provided in this example has good bonding force with the base glaze layer and the protective layer. The selected heating resistor layer is composed of a mixture of HfCxNy and SiC. The proportion of HfCxNy is between 30% and 70%, the thickness is 10 to 500nm, and the resistivity of the mixture is 500 to 4000E-8Ω.m. The selected heating resistor layer is made by PVD or CVD processes. The melting point of HfCxNy can reach above 4000℃, which is much higher than Ta with a melting point of 2996℃ and an oxidation temperature of about 500℃ commonly used in current heating elements. It has been verified that after ultra-long (300s) ablation, HfCxNy ceramics still maintain a near-zero ablation rate and a continuous and stable anti-oxidation protective structure; HfC The thermal expansion coefficient of xNy is 6.73±1e-6 / ℃, and the thermal expansion coefficient of SIC is 4±1e-6 / ℃, which are relatively close, and are also relatively close to the underlying HfO2. The thermal expansion coefficients of traditional heating element materials Ta and SiO2 are 15.8±1e-6 / ℃ and 6.5±1e-6 / ℃ respectively, which are quite different, and are also quite different from the underlying HfO2. The resistivity of HfCxNy is 36.33±2e-8Ω·m, and SIC is insulating. The two can obtain different square resistances by adjusting different proportions to meet different resistance requirements. They are also relatively close to traditional heating element materials Ta (resistivity is 15e-8Ω·m) and SiO2 (insulation), and can form a substitute.

[0034] In this example, the resistance pattern of the heating resistor is a mixture of sputtered resistance layer HfCxNy and SiC. The photolithography process is adopted, photoresist is used as a protective layer, and dry etching is used to form the resistance layer pattern. Commonly used etching gases include Ar, CF4, CHF3, O2, etc.

[0035] In this example, the electrode layer 4 of some electrode conductors adopts a double-layer structure. The lower electrode line 4-1 is made of Hf+Re alloy, the Hf ratio is less than 10%, and the thickness is 0.1-2um; the upper electrode 4-2 is made of Hf+Ir alloy, the Hf ratio is less than 10%, and the thickness is

[0036] 0.05~0.2um, the selected electrode layer 4 is made of PVD or CVD technology, the melting points of Hf+Re are 2227℃ and 3180℃ respectively, which are much higher than the Al with a melting point of about 600℃ commonly used now, the thermal expansion coefficient of Hf+Re is 5.8±1e-6 / ℃ and 6.7±1e-6 / ℃, which are less than 23e-6 / ℃ of Al, and are similar to the expansion coefficient of the heating element in the lower layer, and the Re metal has good plasticity and toughness to ensure that it will not break at high temperature; the resistivity of Hf+Re is 35.7e-8Ω·m and 5.42e-8Ω·m respectively, which is greater than 2.83e-8Ω·m of Al, so it is only limited to use near heating elements with higher temperature requirements, and the proportion of Hf cannot be too high. In order to obtain better anti-oxidation performance, a thin Hf+Ir alloy conductive layer with a thickness of 0.05~0.2um is made outside the Hf+Re alloy. Ir has excellent anti-oxidation performance and can resist oxidation up to 2100℃. The thermal expansion coefficient of Ir is 6.4±1e-6 / ℃, which is similar to the lower electrode 1, and the resistivity is 4.7e-8Ω·m, which is also similar to the lower electrode line.

[0037] In this example, the electrode layer can be realized by a variety of process methods, for example: sputtering the electrode layer Hf+Re alloy and Hf+Ir alloy, using a photolithography process, using a photoresist as a protective layer, and wet etching to form the electrode layer pattern. The wet chemicals use various acid liquids; Method 2, using a photolithography process, using a photoresist to protect the unnecessary image, sputtering the electrode layer Hf+Re alloy and Hf+Ir alloy, removing the photoresist and the electrode layer above, leaving the pattern outside the photoresist to form the electrode layer pattern.

[0038] In this example, the insulating protective film is composed of at least one of a HfO2 & SiN mixture, a HfO2 & SiON mixture, or a HfO2 & SIALON mixture, the proportion of HfO2 is less than 20%, and the total thickness is between 1 and 20 um. SiN is an electrical insulator with a temperature resistance of about 1900°C and a thermal expansion coefficient of 2.35±0.5e-6 / °C; SIALON is an electrical insulator with a melting point greater than 1500°C, a heat shock resistance greater than 900°C, and a thermal expansion coefficient of 2.6±0.5e-6 / °C. Both are relatively excellent temperature-resistant materials, and their expansion coefficients are close to those of HfO2 in the underlying base glaze 2 and HfCxNy in the heating element. The insulating protective film can be made using the Lift-Off process, with bentonite powder configured into a special slurry, and the electrode pattern to be exposed can be covered using a printing process, and an insulating protective film HfO2&SiN mixture or HfO2&SiON mixture or HfO2&SIALON mixture can be sputtered. Finally, the bentonite and the insulating protective film above can be removed to form an insulating protective film pattern.

[0039] In this example, Hf element runs through the entire process from the heat storage layer to the heating element, to the electrode, and then to the protective layer, which can maintain the fusion between the layers.

[0040] The heating resistor described in this example can be made by the following method:

[0041] S1: HfC powder, HfN powder and SIC powder are prepared in a mass ratio of HfC:HfN:SIC=2:3:2. The specific ratio is adjusted according to the resistance value of the print head to be made. The purity of HfC, HfN and SIC is greater than or equal to 99.9%. The prepared HfC powder, HfN powder and SIC powder are refined by ball milling and mixed evenly. The mixed powder is filtered to obtain a powder with a particle size of less than 5um;

[0042] S2: The obtained mixed powder is subjected to plasma sintering. The conditions for plasma sintering are: the temperature in the sintering furnace is 2100-2500°C (the melting points of HfC, HfN, and SIC are 3928°C, 3305°C, and 2827°C, respectively). The plasma sintering temperature does not necessarily need to reach the melting point of the sintered material. Spark plasma sintering (SPS) allows the powder particles to be quickly densified at a temperature below the melting point. Keep warm for 15-20 minutes, the pressure is 35-50MPa, and the vacuum degree is less than 2Pa;

[0043] S3: The sintered material is cut into required sizes and welded to the target base to make a PVD target;

[0044] S4: Using PVD magnetron sputtering process, the specific steps are as follows: direct current (DC) or radio frequency (RF) can be used. Since the material is conductive, DC is preferred for higher sputtering efficiency. The substrate with the base glaze is placed in the cavity, and the vacuum degree in the cavity is set to below 1×10-4Pa. The cavity temperature is heated to 150-300°C, and argon gas is introduced with a pressure of 0.1-5Pa. The film layer is prepared using magnetron sputtering technology. In order to improve the density and adhesion of the material, a direct current pulse method can be further used on the basis of the DC mode, with the conditions of a frequency of 50-150k, a pulse power density of 4-7w / cm2, a duty cycle of 20-45%, and an air pressure of 0.2-0.8Pa. High-power pulsed magnetron sputtering (HIPIMS) technology can also be used, with a pulse power density of 400-1000w / cm2, a frequency of 0.1-5kHz, a duty cycle of 5-20%, and an air pressure of 0.2-1Pa. High-power impulse magnetron sputtering (HIPIMS) is a magnetron sputtering technology that uses higher pulse peak power and lower pulse duty cycle to produce high sputtering metal ionization rate. Due to the short pulse action time, its average power is not high, so the cathode will not increase the target cooling requirements due to overheating. Its peak power is 100 times that of ordinary magnetron sputtering, and the plasma density can be as high as 1018m-3. In addition, this highly ionized beam does not contain large particles, and the generated film is dense and has excellent performance.

[0045] The preparation methods of the HfO2 layer in the base glaze layer and the electrode wire segments (Hf+Re alloy, Hf+Ir alloy) resistant to high energy impact refer to the method of the heating element, and are directly sputtered to the corresponding target material; the electrode can be made by DC or RF magnetron sputtering process if it is a conductive material; the HfO2 layer is made by RF magnetron sputtering process because it is a non-conductive material; the preparation methods of the protective film (HfO2&SiN or HfO2&SiON or HfO2&SIALON) refer to the method of the heating element, and the target material can be a single target, which is made by mixed plasma sintering, or two independent double targets can be used. When two independent targets are sputtered, the method of simultaneous sputtering in the same cavity can be used according to different proportions. Because the target material is non-conductive, the protective film is made by RF magnetron sputtering process.

Claims

1. A heating substrate for a thermal print head resistant to high energy impact, comprising an insulating substrate, an underglaze layer on the insulating substrate, a heating resistor and an electrode wire arranged on the underglaze layer, and a protective layer covering the heating resistor and part of the electrode wire, characterized in that: The electrode wire comprises an electrode wire segment resistant to high-energy impact, wherein the electrode wire segment resistant to high-energy impact is provided with a lower electrode wire and an upper electrode wire, wherein the lower electrode wire is made of a hafnium-rhenium (HfRe) alloy, wherein the thickness of the lower electrode wire is in the range of 0.1-2.0 μm, and the content of hafnium (Hf) in the lower electrode wire is less than 10% of the total mass percentage, and the upper electrode wire is made of a hafnium-iridium alloy, wherein the upper electrode wire is located on the surface of the lower electrode wire, and wherein the thickness of the upper electrode wire is in the range of 0.05-0.2 μm, and the content of hafnium (Hf) in the lower electrode wire is less than 10% of the total mass percentage.

2. The high-energy impact-resistant heating substrate for a thermal print head according to claim 1, characterized in that: The electrode wire also includes a common wire segment connected to the high-energy impact-resistant electrode wire segment, the common wire segment is made of aluminum wire, and the high-energy impact-resistant electrode wire segment is only distributed in an area 0.3 mm away from the heating resistor.

3. The heat generating substrate for a thermal print head resistant to high energy impact according to claim 1, characterized in that: The heating resistor is made of a mixture of HfCxNy and SiC, wherein the proportion of HfCxNy is between 30% and 70%, the thickness of the heating resistor is 10 to 500 nm, and the resistivity of the heating resistor is 500 to 4000E-8Ω.m.

4. The heat generating substrate for a thermal print head resistant to high energy impact according to claim 1, characterized in that: The bottom glaze layer includes a bottom glaze heat storage layer using SiO2 as the main material and a HfO2 layer located on the upper surface of the bottom glaze heat storage layer. The thickness of the bottom glaze heat storage layer is between several um and several hundred um. The thermal conductivity of the bottom glaze heat storage layer is 1±0.5W / mK, and the thermal expansion coefficient is 6.5±1e-6 / ℃. A HfO2 layer with a thickness of 0.1~10um is provided on the surface of the bottom glaze heat storage layer. The thermal conductivity of the HfO2 layer is 1.6~2W / mK, and the thermal expansion coefficient of HfO2 is 6±1e-6 / ℃.

5. The heat generating substrate for a thermal print head resistant to high energy shock according to claim 1, characterized in that: The insulating protective film in the protective layer is composed of at least one of a HfO2&SiN mixture, a HfO2&SiON mixture, or a HfO2&SIALON mixture, the proportion of HfO2 is less than 20%, the total thickness is between 1 and 20 um, SiN is electrically insulating, has a temperature resistance of 1900°C, and a thermal expansion coefficient of 2.35±0.5e-6 / °C, SIALON is electrically insulating, has a melting point greater than 1500°C, is heat-shock-resistant greater than 900°C, and has a thermal expansion coefficient of 2.6±0.5e-6 / °C.

6. The method for manufacturing a heat generating substrate for a thermal print head according to claim 6, wherein: In the manufacturing method of the heating substrate for the thermal print head, the heating resistor is manufactured by the following method: Step 1: Prepare HfC powder, HfN powder and SIC powder in a mass ratio of HfC:HfN:SIC=(1-3):(1-3):(1-2), and the specific ratio is adjusted according to the resistance value of the print head to be made. The purity of HfC, HfN and SIC is greater than or equal to 99.9%. The prepared HfC powder, HfN powder and SIC powder are refined by ball milling and mixed evenly. The mixed powder is filtered to obtain a powder with a particle size of less than 5 um; Step 2: Plasma sintering of the obtained mixed powder, the conditions of plasma sintering are: the temperature in the sintering furnace is 2100-2500° C., the temperature is kept for 15-20 minutes, the pressure is 35-50 MPa, and the vacuum degree is less than 2 Pa; Step 3: The sintered material is cut into required sizes and welded to the target base to make a PVD target; Step 4: Use PVD magnetron sputtering technology to prepare the heating resistor layer by direct current DC or radio frequency RF, put the substrate with base glaze into the cavity, set the vacuum degree in the cavity to below 1×10-4Pa, heat the cavity temperature to 150~300℃, and introduce argon gas with a pressure of 0.1~5Pa.

7. The method for manufacturing a heat generating substrate for a thermal print head according to claim 7, wherein: In step 4, since the material is conductive, direct current (DC) is selected and a direct current pulse is used with the conditions of a frequency of 50-150k, a pulse power density of 4-7w / cm2, a duty cycle of 20-45%, and an air pressure of 0.2-0.8Pa.

8. A method for manufacturing a heating substrate for a thermal print head as claimed in any one of claims 1 to 5, characterized in that: The heating element resistance layer resistant to high energy impact adopts photolithography technology, uses photoresist as a protective layer, and forms the resistance layer pattern by dry etching, and the etching gas is selected from Ar, CF4, CHF3, and O2.

Citation Information

Patent Citations

  • A long-lasting, ablation-resistant, ultra-high melting point nitrogen-containing carbide ultra-high temperature ceramic and its applications

    CN111072388B

  • Electromechanical transducing device and manufacturing method thereof, and liquid droplet discharging head and liquid droplet discharging apparatus

    CN103210515A

  • Force sensor controlled conductive heating element

    CN115427233A

  • Energy-impact-resistant heating substrate for thermal printing and preparation method thereof

    CN119489626A

  • Electromechanical conversion element, droplet ejection head including electromechanical conversion element, and ink jet printer including droplet ejection head

    JP2013062357A

Cited By

  • High-energy-impact-resistant heating substrate for thermal printing head and manufacturing method thereof

    CN119427951A

  • Heating substrate for thermal print head resistant to high energy impact and its manufacturing method

    CN119427951B

  • Energy-impact-resistant heating substrate for thermal printing and preparation method thereof

    CN119489626A

  • Energy shock resistant heating substrate for thermal print head and preparation method thereof

    CN119489626B